ANTIBACTERIAL EFFICACY OF 6% GREEN TEA EXTRACT AND 2% CHLORHEXIDINE AGAINST ENTEROCOCCUS FAECALIS BIOFILM IN VITRO - REFLAN, FITRI; MEIDYAWATI, RATNA; INDRAWATI, DARU (International Journal of Applied Pharmaceutics, 2019)
Objective: This study aimed to compare the antibacterial efficacy of green tea extract to chlorhexidine 2% against Enterococcus faecalis biofilm using real-time polymerase chain reaction (RT-PCR). Methods: E. faecalis strain ATCC 29212 colonies were collected from overnight cultures grown on brain–heart infusion agar (BHIA) and resuspended at 108 CFU/ml according to a 0.5 McFarland standard. Aliquots of bacterial suspension (50 μl) were then inoculated onto sterile nitrocellulose filter discs place on BHIA and incubated aerobically at 37°C for 72 h. After incubation, the discs were removed, transferred into 10-ml phosphate-buffered saline (PBS) to loosen planktonic bacteria, and then incubated for 10 min at 37°C in 10 ml of 6% green tea extract, 2% chlorhexidine, or sterile PBS (control). Surviving E. faecalis cells were then quantified by RT-PCR. Results: Green tea extract reduced bacterial survival compared to control but was not as effective as chlorhexidine 2%. Conclusion: Green tea extract may help reduce oral E. faecalis biofilm. Moreover, specific antimicrobial compounds in green tea extract such as epigallocatechin-3-gallate should be tested as non-toxic alternatives to chlorhexidine.